Do Shopping Lifestyle, Price Discount, and Positive Emotion Influence Impulse Buying? An Empirical Analysis of the Indonesian Fashion Industry - Fikrul Umam Zein; Effed Darta Hadi (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to examine the effect of shopping lifestyle, price discount, and positive emotion on impulse buying, as well as the mediating role of positive emotion in the relationship between shopping lifestyle and price discount on impulse buying in the Indonesian fashion industry.Method: This research employs a quantitative approach by collecting primary data through questionnaires distributed via Google Forms. The study involved 350 Erigo customers who had made impulsive purchases of Erigo products, selected using the incidental sampling method. The collected data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, utilizing SmartPLS 3 software.Result: The findings of this study indicate that shopping lifestyle and positive emotion have a direct, positive, and significant impact on impulse buying. However, price discount does not directly influence impulse buying. Nevertheless, positive emotion successfully mediates the effect of price discount on impulse buying and also mediates the effect of shopping lifestyle on impulse buying positively and significantly.Practical Implications for Economic Growth and Development: The results of this study provide strategic insights for fashion brands, particularly local fashion brands, to enhance sales by leveraging internal factors such as positive emotion and shopping lifestyle, as well as external factors like price discounts. These strategies can increase consumer purchases and, in turn, contribute to economic growth.